(untitled) (San Prancisco, CA., 2006)
The Minister's Manual is the single most comprehensive resource for preaching and worship available. Filled with completely new material for 2006, this nondenominational guide is the best source for sermons, prayers, insights, and inspiration for all???from pastors and lay leaders to Sunday school teachers and choir directors. The large format makes it easy to use.
Keywords: Diplomats,Ngoại giao; Minister,Cấp bộ trưởng; Manual